Clinical Impact of Radioguided Localization in the Treatment of Solitary Pulmonary Nodule: A 20-Year Retrospective Analysis. (May 2018) - Manca, Gianpiero; Davini, Federico; Tardelli, Elisa; De Liperi, Annalisa; Falaschi, Fabio; Melfi, Franca; Colletti, Patrick M.; Rubello, Domenico; Volterrani, Duccio; Boni, Giuseppe
Abstract : Purpose: Incidental solitary pulmonary nodules (SPNs) have become an increasingly common CT finding worldwide. Although there are currently many imaging strategies for evaluating SPNs, the differential diagnosis and management of SPNs remains complex because of overlap between benign and malignant processes. Moreover, transbronchial or percutaneous CT-guided biopsies do not always allow definitive diagnoses. In such cases, video-assisted thoracic surgery (VATS) has become the preferred surgical procedure for diagnosis and, in selected cases, for treatment of indeterminate SPNs. The difficulties in localizing smaller, deeper, and ground-glass nodules have been approached with different techniques. The aim of this study was to report 20 years of experience with radioguided thoracoscopic resection of SPNs at the Regional Centre of Nuclear Medicine of Pisa. Methods: Three hundred ninety-five patients with SPNs less than 2 cm and deeper than 5 mm below the visceral pleura underwent CT-guided injection of a suspension composed of 0.1 to 0.2 mL 99m Tc-labeled human albumin macroaggregates ( 99m Tc-MAA) and of 0.2 to 0.3 mL of nonionic contrast medium into or adjacent to the SPN. During VATS, the pulmonary area with the highest target/background ratio identified by an 11-mm-diameter collimated thoracoscopic gamma probe was resected. Results: From 1997 to 2016, approximately 395 patients with SPN underwent VATS wedge resection using the radioguided technique. Mean SPN size was 13 mm (range, 5–20 mm) with mean distance of 15 mm (range, 6–39 mm) from the visceral pleura. Mean VATS procedural time was 40 minutes (range, 20–90 minutes), with an average time of 3 minutes (range, 1–5 minutes) to localize the nodule. Neither mortality nor major perioperative complication was reported. The success rate of VATS with radioguidance in our series was 99%. Histological examination revealed 206 benign lesions (52%), 59 primary lung tumors (15%), and 130 metastatic nodules (33%). Conclusions: This study demonstrates that radioguided SPN localization by VATS is a feasible, safe, and rapid procedure with highly successful rate of SPN resection.